2013
DOI: 10.12692/ijb/3.3.9-14
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic effects of some Lamiaceae on seed germination and seedling growth of dodder (Cuscuta campestris Yunck.)

Abstract: Dodder (Cuscuta campestris Yunck.) is one of the parasitic weeds that cause yield losses of many crops and orchards. Control of this weed is very difficult. This experiment was carried out to assay the effects of different concentrations [0 (distilled water as a control), 1.25%, 2.5%, and 5% (gram powder of plant per 100 ml of distilled water)] of lavender (Lavandula vera DC.), rosemary (Rosmarinus officinalis L.), garden sage (Salvia officinalis L.), thyme (Thymus vulgaris L.), and common balm (Melisa officin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
3
3
0
Order By: Relevance
“…The results showed a reduced germination percentage with increasing concentration of allelochemicals from D.stramonium across all the measured weeds. These results concur with the findings of many authors (Hassannejad and Ghafarbi, 2013;Yu et al, 2003;Elisante et al, 2013;Oyun, 2006;Alam and Islam, 2002). D. stramonium allelochemicals contains chemicals that retard the metabolism of food reserves in the seed (Levit et al, 1984) and the secondary effects of these processes include reduced germination and early growth of radicles (Levitt and Lovetti, 1984).…”
Section: Discussionsupporting
confidence: 89%
“…The results showed a reduced germination percentage with increasing concentration of allelochemicals from D.stramonium across all the measured weeds. These results concur with the findings of many authors (Hassannejad and Ghafarbi, 2013;Yu et al, 2003;Elisante et al, 2013;Oyun, 2006;Alam and Islam, 2002). D. stramonium allelochemicals contains chemicals that retard the metabolism of food reserves in the seed (Levit et al, 1984) and the secondary effects of these processes include reduced germination and early growth of radicles (Levitt and Lovetti, 1984).…”
Section: Discussionsupporting
confidence: 89%
“…These results may be due to the superior effect of both eucalyptus oil and Trichoderma harzianum, which has resulted in increased cabbage and cauliflower vegetative growth characteristics (Table 2 and 3). These results agree with those of Niakan and Saberi (2009), also Cumagun (2012), Rehman et al (2012), and Hassannejad & Ghafarbi (2013).…”
Section: Cauliflower Plantssupporting
confidence: 90%
“…These results agree with those of Niakan and Saberi (2009) on phalaris weed who stated that eucalyptus increased root and shoot length. Also, Hassannejad and Ghafarbi (2013) revealed that eucalyptus caused increases in seed germination. Also, Rehman et al (2012) stated that Trichoderma treatments increased seed germination and improved plant growth vigor on cauliflower.…”
Section: Horticulture Parameters Vegetative Growth Cabbage Plantsmentioning
confidence: 99%
“…This shows that water is necessary for germination to take place; it triggers biochemical reactions. Seed germination on all tested species might have been inhibited by the presence of aqueous thorn apple extracts; these results were in line with those by Hassannejad and Ghafarbi (2013). This could be attributed to reduced water uptake by the seeds in the presence of allelochemicals found in thorn apple (ELshora et al, 2015a).…”
Section: Discussionsupporting
confidence: 78%